The answer would be 75 width
Answer:
D
Step-by-step explanation:
The radius r is the distance from the centre to a point on the circle.
Calculate r using the distance formula
r = √ (x₂ - x₁ )² + (y₂ - y₁ )²
with (x₁, y₁ ) = (0, 0) and (x₂, y₂ ) = (- 5, - 12)
r = ![\sqrt{(-5-0)^2+(-12-0)^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%28-5-0%29%5E2%2B%28-12-0%29%5E2%7D)
= ![\sqrt{(-5)^2+(-12)^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%28-5%29%5E2%2B%28-12%29%5E2%7D)
= ![\sqrt{25+144}](https://tex.z-dn.net/?f=%5Csqrt%7B25%2B144%7D)
= ![\sqrt{169}](https://tex.z-dn.net/?f=%5Csqrt%7B169%7D)
= 13 → D
Answer:
We conclude that the rule for the table in terms of x and y is:
Step-by-step explanation:
The table indicates that there is constant change in the x and y values, meaning the table represents the linear function the graph of which would be a straight line.
We know the slope-intercept form of the line equation
y = mx+b
where m is the slope and b is the y-intercept.
Taking two points
Finding the slope between (-2, -4) and (-1, -1)
![\mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cmathrm%7BSlope%7D%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
![\left(x_1,\:y_1\right)=\left(-2,\:-4\right),\:\left(x_2,\:y_2\right)=\left(-1,\:-1\right)](https://tex.z-dn.net/?f=%5Cleft%28x_1%2C%5C%3Ay_1%5Cright%29%3D%5Cleft%28-2%2C%5C%3A-4%5Cright%29%2C%5C%3A%5Cleft%28x_2%2C%5C%3Ay_2%5Cright%29%3D%5Cleft%28-1%2C%5C%3A-1%5Cright%29)
![m=\frac{-1-\left(-4\right)}{-1-\left(-2\right)}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-1-%5Cleft%28-4%5Cright%29%7D%7B-1-%5Cleft%28-2%5Cright%29%7D)
![m=3](https://tex.z-dn.net/?f=m%3D3)
We know that the y-intercept can be determined by setting x = 0 and finding the corresponding y-value.
Taking another point (0, 2) from the table.
It means at x = 0, y = 2.
Thus, the y-intercept b = 2
Using the slope-intercept form of the linear line function
y = mx+b
substituting m = 3 and b = 2
y = 3x+2
Therefore, we conclude that the rule for the table in terms of x and y is:
Answer:
Step-by-step explanation:
= x²(-3 +5) +y²(2 -3) +5xy -2y
= 2x² -y² +5xy -2y
a) there are 4 terms in the simplified expression
b) 2 terms have negative coefficients (-y² and -2y)
Answer:
first one is A and the second one is B.
Step-by-step explanation: